Selective Sensing of Proteins Using Aptamer Functionalized Nanopore Extended Field‐Effect Transistors. Issue 11 (16th July 2020) - Ren, Ren; Wang, Xiaoyi; Cai, Shenglin; Zhang, Yanjun; Korchev, Yuri; Ivanov, Aleksandar P.; Edel, Joshua B.
Abstract: The ability to sense proteins and protein‐related interactions at the single‐molecule level is becoming of increasing importance to understand biological processes and diseases better. Single‐molecule sensors, such as nanopores have shown substantial promise for the label‐free detection of proteins; however, challenges remain due to the lack of selectivity and the need for relatively high analyte concentrations. An aptamer‐functionalized nanopore extended field‐effect transistor (nexFET) sensor is reported here, where protein transport can be controlled via the gate voltage that in turn improves single‐molecule sensitivity and analyte capture rates. Importantly, these sensors allow for selective detection, based on the choice of aptamer chemistry, and can provide a valuable addition to the existing methods for the analysis of proteins and biomarkers in biological fluids. Abstract : A novel nanopore‐based field‐effect‐transistor platform for selective single‐molecule sensing is presented. The surface is aptamer functionalized and can be used for efficient label‐free detection of single proteins. By applying a gate voltage it becomes possible to detect proteins at low picomolar concentrates, with improved signal‐to‐noise, higher capture rates, and lower translocation speeds compared to more conventional nanopore‐based platforms.